Folklore-Based Virtual Reality as a Teaching Media in the Secondary School Viewed From its Implication and Multimodal Aspects - Herdiawan, Rama Dwika; Afrianto, Afrianto; Nurhidayat, Eka; Nurhidayah, Yayah; Rofi’i, Agus (IJLECR (International Journal of Language Education and Cultural Review), 2023)
This research article explores folklore-based virtual reality (VR) as a teaching medium in secondary schools, examining its effectiveness and impact on students’ learning experiences. Taking advantage of virtual reality (VR) in education has several benefits, including enhancing students’ learning experiences, facilitating more effective comprehension of concepts, and preparing students for the demands of an ever-evolving digital society. Drawing upon the multimodal discourse analysis framework, the study investigates how combining virtual reality technology and folklore narratives can enhance students’ engagement, understanding, and retention of educational content. The findings highlight the potential of folklore-based VR as a powerful tool for immersive and interactive learning while shedding light on the multimodal aspects of the discourse generated through this medium. Educators can enhance the learning experience and foster a deeper understanding of cultural heritage and identity by integrating folklore-based virtual reality as a teaching medium. Moreover, Folklore-based virtual reality can encourage critical thinking skills as students navigate through complex narratives, make decisions, and solve problems within the virtual environment. Furthermore, exposure to diverse folklore stories and characters can promote empathy and understanding of different cultures, fostering a more inclusive and tolerant society. Integrating virtual reality (VR) technology into English education and literary resources presents promising prospects for students to actively interact with books through novel approaches, augmenting their understanding, language proficiency, and general admiration for literature. The research contributes to the growing field of educational technology by demonstrating the benefits of folklore-based VR as a pedagogical approach in secondary education.